Gracilis Muscle Interposition for Treatment of Complex Anal Fistula: Experience With 119 Consecutive Patients. Issue 7 (July 2021) - Yellinek, Shlomo; Sousa, Cesar Barros; Gilshtein, Hayim; Strassmann, Victor; da Silva, Giovana; Wexner, Steven D.
Abstract : BACKGROUND: Treatment of complex anal fistula is challenging, often mandating multiple procedures. The gracilis muscle has been used to treat perineal fistulas and to repair perineal defects. OBJECTIVE: This study aims to report the results of gracilis muscle interposition for complex anal fistula, including prognostic factors for success. DESIGN: This is a retrospective analysis of a prospective database for patients who underwent gracilis muscle interposition for complex anal fistula from 2000 to 2018. SETTING: Patient demographics, operative data, and postoperative outcome were obtained from medical records. Office visits were used for follow-up. PATIENTS: All patients who underwent gracilis muscle interposition for complex anal fistula were included. Patients who underwent gracilis muscle interposition for reasons other than complex anal fistula were excluded. MAIN OUTCOME MEASURES: The primary outcome measured was the healing of complex anal fistula following gracilis muscle interposition and following additional procedures, when needed. RESULTS: A total of 119 patients (60 men, 59 women; median age: 56 (21–85) years) were included. The initial success rate of gracilis muscle interposition was 42%; the final success rate if additional procedures were undertaken was 92%. Overall success rate was 32.2% in women and 51.6% in men. Univariate analysis revealed that sex ( p = 0.0315) and bed rest >3 days ( p = 0.0078) were significant poor prognostic factors for failure, whereas the multivariate logistic regression model showed that length of bed rest >3 days was a significant poor prognostic factor for failure. In the female subgroup, multivariate analysis showed that bed rest ≥3 days was a significant poor prognostic factor, whereas in the male population there was no significant prognostic factor. LIMITATION: This study was limited by its retrospective nature and the heterogeneity of patients. CONCLUSION: Although initial success is <50%, the ultimate success after gracilis muscle interposition and other subsequent procedures is >90%. Patients must be preoperatively counseled that additional procedures will probably be required to achieve successful fistula closure. Furthermore, prolonged bed rest should be avoided after gracilis muscle interposition. See Video Abstract at http://links.lww.com/DCR/B551 . INTERPOSICIÓN DEL MÚSCULO GRACILIS PARA EL TRATAMIENTO DE LA FÍSTULA ANAL COMPLEJA: EXPERIENCIA CON 119 PACIENTES CONSECUTIVOS: ANTECEDENTES: El tratamiento de la fístula anal compleja es un desafío que a menudo requiere de múltiples procedimientos quirúrgicos. El músculo gracilis se ha utilizado para tratar fístulas y reparar defectos perineales. OBJETIVO: Informar los resultados de la interposición del músculo gracilis para la fístula anal compleja, incluyendo los factores pronósticos para un tratamiento exitoso. DISEÑO: Se efectuó un análisis retrospectivo obtenido de una base de datos prospectiva para pacientes sometidos a interposición del músculo gracilis por fístula anal compleja del 2000 al 2018. METODO: Los datos demográficos de los pacientes, la información del procedimiento quirúrgico y los resultados postoperatorios se obtuvieron de los expedientes clínicos; el seguimiento se llevó a cabo por medio de visitas al consultorio. PACIENTES: Se incluyeron todos los pacientes sometidos a interposición del músculo gracilis por fístula anal compleja; Se excluyeron los pacientes que se sometieron a interposición del músculo gracilis por motivos distintos a la fístula anal compleja. CRITERIOS DE EVALUACION DE LOS RESULTADOS: Curación de una fístula anal compleja después de la interposición del músculo gracilis y procedimientos adicionales, cuando fueron necesarios. RESULTADOS: Se estudiaron un total de 119 pacientes [60 hombres, 59 mujeres; con media de edad de 56 (21-85) años]. La tasa de éxito inicial de la interposición del músculo gracilis fue del 42%; La tasa de éxito final cuando realizaron procedimientos adicionales fue del 92%. La tasa de éxito global fue del 32, 2% en mujeres y del 51, 6% en hombres. El análisis univariado reveló que el género ( p = 0, 0315) y el reposo en cama > 3 días ( p = 0, 0078) en forma significativa fueron factores de pronóstico bajo para el fracaso, mientras que el modelo de regresión logística multivariable mostró que la duración del reposo en cama> 3 días fue un factor de pronóstico significativamente bajo para fracaso. En el subgrupo de mujeres, el análisis multivariado mostró que el reposo en cama ≥3 días fue un factor de pronóstico significativamente bajo, mientras que en la población masculina no hubo un factor pronóstico significativo. LIMITACIÓN: Carácter retrospectivo y heterogenicidad de los pacientes. CONCLUSIÓN: Aunque el éxito inicial es <50%, el éxito final después de la interposición del músculo gracilis y otros procedimientos posteriores es > 90%. Se debe aconsejar a los pacientes antes de la operación que probablemente se requieran procedimientos adicionales para lograr el cierre exitoso de la fístula. Además, debe evitarse el reposo prolongado en cama después de la interposición del músculo gracilis. Consulte Video Resumen en http://links.lww.com/DCR/B551 .